(untitled) (Journal of Advanced Research in Social Sciences, 2024)
This study investigated the effects of a brief mindfulness-based stress reduction (MBSR) program on Emotional Intelligence (EI) and job satisfaction among teachers in Saudi Arabia. Given the increasing stress and psychological challenges facing educators, improving EI and stress management techniques is crucial. The primary research questions were: (1) Does participation in MBSR improve EI among male teachers? (2) Does MBSR reduce perceived stress and enhance job satisfaction? A quasi-experimental nonequivalent group pretest-posttest design was utilized, involving 100 Saudi teachers divided into experimental and control groups. Over three weeks, the experimental group engaged in the MBSR program, while the control group received no intervention. EI, mindfulness, job satisfaction, and perceived stress levels were assessed using various measures. Statistical analyses, including descriptive, inferential, and mediation analyses, were conducted to evaluate the effectiveness of the MBSR program. Results indicated that the MBSR group exhibited improved EI, with higher scores for emotional attention, clarity, and repair than the control group. Furthermore, the experimental group showed significant increases in mindfulness and notable reductions in perceived stress levels. Mediation analysis demonstrated that mindfulness and perceived stress partially mediated the relationship between EI and teacher job satisfaction. These findings underscore the potential of MBSR to improve teacher well-being and job performance. The study recommends incorporating MBSR into training programs to equip educators with tools to manage stress, increase awareness, and improve workplace satisfaction. This approach aligns with Saudi Arabia’s Vision 2030 initiatives, promoting a more positive educational environment.